(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of fungal infections of the skin and its appendages (hair and nails) among patients presenting with clinically suspicious lesions at Hai Phong Dermatology Center in 2025. To describe various factors associated with the prevalence of dermatomycosis and its appendages in the study population. Subjects and Methods: A cross-sectional descriptive study was conducted on 394 patients with clinical lesions suggestive of cutaneous fungal infection at Hai Phong Dermatology Center from October to December 2025. Results: The findings indicated a prevalence rate of 64% for fungal infections of the skin and its appendages. Males exhibited a higher infection rate than females (58.7% vs. 41.3%). The 20–39 age group accounted for the highest proportion of cases at 32.5%. Regarding occupation, the "Other" category showed the highest infection rate at 42.9%. Statistical analysis revealed that individuals with a sebaceous (oily) skin constitution and hyperhidrosis (excessive sweating) had a 2.2-fold and 1.67-fold increased risk of infection, respectively, compared to other groups. Behavioral and environmental factors, such as sharing personal attire and pet ownership, increased the risk of infection by approximately 1.8 times. Notably, patients with direct contact with infected individuals or those with a family history of dermatomycosis faced a 2.2-fold higher risk compared to those without such exposure. Conclusion: Dermatomycosis and its appendages remain highly prevalent (64%), primarily affecting males, the 20–39 age group, and those in the "Other" occupational category. Sebaceous skin type, hyperhidrosis, close contact with infected persons, the habit of sharing personal items, and pet ownership are critical associated factors that significantly elevate the risk of fungal infections of the skin and its dependent structures.